Oligodendrogenesis and myelination tracing in a CRISPR/Cas9-engineered brain microphysiological system - Romero, July Carolina; Berlinicke, Cynthia; Chow, Sharon; Duan, Yukan; Wang, Yifei; Chamling, Xitiz; Smirnova, Lena (Frontiers in Cellular Neuroscience, 2023)
Oligodendrocytes (OLs) are the myelin-forming cells of the central nervous system (CNS). Although OLs can be differentiated from human-induced pluripotent stem cells (hiPSCs), the in vitro modeling of axon myelination in human cells remains challenging. Brain organoids are complex three-dimensional (3D) cultures that offer an ideal system to study this process as OLs differentiate in a more in vivo-like environment; surrounded by neurons and astrocytes, which support the myelination of axons. Here, we take advantage of CRISPR/Cas9 technology to generate a hiPSC line in which proteolipid protein 1 (PLP1), an OLs marker, is tagged with super-fold GFP (sfGFP). While generating the PLP1-sfGFP reporter, we used reverse transfection and obtained higher Knock-In (KI) efficiency compared to forward transfection (61-72% vs. 46%). After validation of the KI and quality control of the PLP1-sfGFP line, selected clones were differentiated into brain organoids, and the fidelity, specificity, and function of the tagged PLP protein were verified in this model. We tracked different stages of oligodendrogenesis in the verified lines based on PLP1-sfGFP+ cells’ morphology, and the presence of PLP1-sfGFP surrounding axons during brain organoid differentiation. Finally, we challenged the brain organoids with cuprizone and quantified changes in both the percentage of PLP1-sfGFP expressing cells and the intensity of GFP expression. This work demonstrates an efficient method for generating hiPSC KI lines and the description of a new model to study OL differentiation, migration, and maturation both during in vitro neurodevelopment as well as in response to environmental chemicals or disease-associated stressors.